Perbandingan Peta Pengendali Rata-rata Bergerak Dengan Peta Pengendali Rata-rata Bergerak Geometrik - Nurdayanti Nurdayanti; Darnah Andi Nohe; Rito Goejantoro (Program Studi Statistika FMIPA Universitas Mulawarman, 2016)
The Moving Average Control Chart is a control chart of data observation for small average shift process. The Geometric Moving Average Control Chart is a control chart of specific weight, making it more effective in detecting the smallest change in process. The purpose of this study is to determine whether the wood width which produced by Suryadi Moulding are controlled by Moving Average and Geometric Moving Average Control Chart, and between the two control chart the research want to know which is the best chart.Based on the results of research in the wood width data obtained that the Moving Average and Geometric Moving Average Control Chart there are no points on the outside of the control limits so that it can be concluded that the wood width which produced by Suryadi Moulding Samarinda on the under controlled conditions. If viewed from the width limit controller chart because of the wide limit on the Geometric Moving Average Control Chart is better than the Moving Average Control Chart because the wide limit on the Geometric Moving Average Control Chart is narrower so the result of this control chart is more accurate.